Tata Kelola untuk Pertumbuhan: Menjelajahi Kaitan Antara Tata Kelola Perusahaan dan Kinerja Keuangan di Perusahaan Penyelenggara Acara - Yuniarti Yuniarti; Uun Sunarsih (Journal of Accounting, Management, and Economics Research (JAMER), 2026)
This study explores the role of corporate governance in improving the financial performance of event organizer companies, focusing on PT Perkasa Objektif Visitama. The study is motivated by the increasing need for event organizers to strengthen governance practices in response to intense competition, business uncertainty, and the unique characteristics of project-based creative industries. Using a qualitative approach with an ethnomethodology design, data were collected through in-depth interviews, observations, and document analysis to understand how governance practices are implemented in daily organizational activities. The findings indicate that corporate governance is practiced through four key pillars: ethical behavior, accountability, transparency, and sustainability. These governance practices contribute to stronger internal control, enhanced trust among stakeholders, improved operational efficiency, better cash flow management, and increased profitability. The study further reveals that corporate governance functions not only as a monitoring mechanism but also as a strategic business approach that supports organizational resilience and long-term competitiveness. The study concludes that effective corporate governance plays a vital role in enhancing financial performance and business sustainability in the event organizer industry. Managerially, companies should strengthen governance practices to improve stakeholder confidence, operational effectiveness, and sustainable growth.